2016
DOI: 10.1002/path.4831
|View full text |Cite|
|
Sign up to set email alerts
|

Renal recruitment of B lymphocytes exacerbates tubulointerstitial fibrosis by promoting monocyte mobilization and infiltration after unilateral ureteral obstruction

Abstract: Renal fibrosis is a significant threat to public health globally. Diverse primary aetiologies eventually result in chronic kidney disease (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
3
35
2
Order By: Relevance
“…Tapmeier et al [40] found a critical role for CD4(+) Kidney Dis 2020;6:150-156 DOI: 10.1159/000506201 T cells in kidney fibrosis using lymphopenic RAG(-/-) mice after ureteric obstruction. In addition, early-stage accumulation of B cells in the kidney accelerated monocyte/macrophage mobilization and infiltration and aggravated the renal fibrosis [41].…”
Section: Lvs Serve As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 99%
“…Tapmeier et al [40] found a critical role for CD4(+) Kidney Dis 2020;6:150-156 DOI: 10.1159/000506201 T cells in kidney fibrosis using lymphopenic RAG(-/-) mice after ureteric obstruction. In addition, early-stage accumulation of B cells in the kidney accelerated monocyte/macrophage mobilization and infiltration and aggravated the renal fibrosis [41].…”
Section: Lvs Serve As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 99%
“…These chemokines are responsible for the recruitment of inflammatory cells, which, when activated, produce more cytokines to sustain and enhance inflammation. MCP-1 recruits macrophages into renal interstitium [27,28,29]. Our study showed that Ruxolitinib treatment reduced MCP-1 expression as well as macrophage infiltration in the obstructed kidneys.…”
Section: Discussionmentioning
confidence: 52%
“…However, some studies suggested that B cell infiltration after AKI might hinder normal wound healing 31 . Interestingly, recent studies also suggested that infiltrated lymphocytes directly affected renal fibrosis by increasing levels of TGF-β 1 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%